COMMUNICATION PATTERN BETWEEN FEMALE BREADWINNERS AND THEIR CHILDREN - Chatia Hastasari (Informasi, 2019)
This study examines the communication pattern between female breadwinners and their children and the barriers in that communication process. This qualitative study was carried out among 12 female breadwinners from low-income families in Wedomartani Village, Ngemplak, Sleman, Special Region of Yogyakarta. It is drawn from the study that, first, there is good interpersonal communication between a female breadwinner and her children. It is clearly seen as all factors leading to an effective interpersonal communication are fulfilled, namely a) openness – the mother is actively creating a pleasant conversation so that her children will feel more comfortable in telling her everything that happens to them; b) empathy – the mother instills a sense of independence and respect for others in her children; and c) positive behaviors – the mother has a strong commitment to improve her family’s condition as shown in all her positive behaviors. Second, as the mother and her children can interchangeably be the communicator (sender) or the communicant (recipient) of information, this communication is categorized as direct (face-to-face), either one-way or two-way. Third, the barrier existing in the communication process between a female breadwinner and her children is mainly related to the mother’s limited time available to do her main duties as a mother, causing her housework to become abandoned. Another obstacle in this communication process is due to the children’s psychological condition that is affected by the lack or even the absence of father’s roles in their family, leading to an unstable emotion.Penelitian ini bertujuan untuk mengetahui bagaimana pola komunikasi wanita sebagai kepala keluarga dengan anaknya dan apa saja hambatan yang terjadi pada proses komunikasi antara wanita kepala keluarga dengan sang anak. Penelitian ini menggunakan pendekatan kualitatif dengan sumber data utama para wanita kepala keluarga miskin di desa Wedomartani, Ngemplak, Sleman yang berjumlah 12 informan. Hasil penelitian ini adalah 1) komunikasi interpersonal yang terjalin antara ibu sebagai wanita kepala keluarga dengan sang anak sudah berjalan dengan baik. Hal itu tampak dari pemenuhan faktor-faktor yang dapat memengaruhi komunikasi interpersonal agar menjadi lebih efektif diantaranya a) Keterbukaan yang ditandai dengan adanya peran aktif sang ibu dalam proses komunikasi agar sang anak merasa nyaman bercerita segala hal; b) Empati yang ditanamkan oleh sang ibu pada diri sang anak adalah kemandirian dan rasa menghargai orang lain terutama orang tua; dan c) Perilaku positif yang ditunjukkan dari komitmen yang kuat sang ibu dalam memperbaiki kondisi keluarga. 2) pola komunikasi interpersonal yang terjadi bersifat langsung (tatap muka) baik satu arah maupun dua arah. Hal ini tampak dari posisi komunikator (pengirim pesan) dan komunikan (penerima pesan) dapat dilakukan oleh ibu maupun anak. Dan 3) hambatan dalam proses komunikasi yang terjalin antara ibu sebagai wanita kepala keluarga dengan anaknya saat berinteraksi adalah minimnya waktu yang dimiliki oleh sang ibu menyebabkan tugas dan kewajiban utamanya sebagai seorang ibu di rumah menjadi terbengkalai dan hambatan lainnya adalah kondisi psikologis anak yang mengalami kekurangan atau bahkan kehilangan sosok ayah dalam keluarga menyebabkan emosinya menjadi tidak stabil.